2008
DOI: 10.1002/ejic.200800704
|View full text |Cite
|
Sign up to set email alerts
|

Reactions of (Me2C)(Me2Si)[(η5‐C5H3)­Mo(CO)3]2 with Phosphanylalkynes: Rearrangement of Phosphanylalkynes into Phosphido‐Substituted Vinylidenyl Ligands by Cleavage of the P–C(alkyne) Bond and Formation of a P–C(alkene) Bond

Abstract: This article deals with the thermal reactions of the doubly bridged bis(cyclopentadienyl) dinuclear molybdenum complex (Me2C)(Me2Si)[(η5‐C5H3)Mo(CO)3]2 (1) with a series of phosphanylalkynes PhnP(C≡CR)3–n (n = 2, 1, 0; R = Ph, Fc). In addition to the complex (Me2C)(Me2Si)[(η5‐C5H3)2Mo2(CO)4(μ‐η2‐η2(⟂)‐R1C≡CR2)] [R1 = Ph, R2 = Ph2P, 2; R1 = Ph, R2 = Ph2P(O), 4; R1 = Ph, R2 = PhP(C≡CPh), 6; R1 = Fc, R2 = PhP(C≡CFc), 8; and R1 = Fc, R2 = PhP(O)(C≡CFc), 10], in which the phosphanylalkynes acted as disubstituted ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 72 publications
0
2
0
Order By: Relevance
“…13 Li et al have synthesised [(Me 2 C)(Me 2 Si)(h 5 -C 5 H 3 ) 2 Mo 2 (CO) 4 m-h 2 :h 2 -PPh n (C^CR) 3Àn ] from reactions of the doubly bridged bis(cyclopentadienyl) dinuclear molybdenum complex, [(Me 2 C)(Me 2 Si)(h 5 -C 5 H 3 ) Mo(CO) 3 ] 2 with a series of phosphinoalkynes PPh n (C^CR) 3Àn (n ¼ 2, 1, 0; R ¼ Ph, Fc). 3 Recently, synthesis and electrochemical investigation of ferrocenylethynylphosphine linked to Pt(II) complexes have been reported. 14 Complexes [{(FcC^C) n PPh 3Àn } 2 PdCl 2 ] (n ¼ 1-3) have been shown to be superior pre-catalysts in Suzuki-Miyaura and Heck-Mizoroki carbon-carbon cross-coupling reactions compared to standard [Pd(OAc) 2 (PPh 3 ) 2 ] systems, which has been attributed to unique electronic property of ferrocene.…”
Section: Introductionmentioning
confidence: 99%
“…13 Li et al have synthesised [(Me 2 C)(Me 2 Si)(h 5 -C 5 H 3 ) 2 Mo 2 (CO) 4 m-h 2 :h 2 -PPh n (C^CR) 3Àn ] from reactions of the doubly bridged bis(cyclopentadienyl) dinuclear molybdenum complex, [(Me 2 C)(Me 2 Si)(h 5 -C 5 H 3 ) Mo(CO) 3 ] 2 with a series of phosphinoalkynes PPh n (C^CR) 3Àn (n ¼ 2, 1, 0; R ¼ Ph, Fc). 3 Recently, synthesis and electrochemical investigation of ferrocenylethynylphosphine linked to Pt(II) complexes have been reported. 14 Complexes [{(FcC^C) n PPh 3Àn } 2 PdCl 2 ] (n ¼ 1-3) have been shown to be superior pre-catalysts in Suzuki-Miyaura and Heck-Mizoroki carbon-carbon cross-coupling reactions compared to standard [Pd(OAc) 2 (PPh 3 ) 2 ] systems, which has been attributed to unique electronic property of ferrocene.…”
Section: Introductionmentioning
confidence: 99%
“…Alkynylphosphines PR 3-n (C∫CR¢) n have been actively investigated for many years, not only due to their wide versatility and flexibility as polyfunctional ligands, 1-17 but also because they exhibit an interesting chemical reactivity when they are coordinated to metal centers. 1-4,10,17- 45 Previous investigations have shown that these ligands participate in P-C bond cleavage and insertion or intramolecular coupling processes. In particular, in this area we 10,38,39 and others 28,40-43 have shown that the proximity of two acetylenic groups on alkynylphosphinebased complexes, induces intramolecular coupling reactions.…”
Section: Introductionmentioning
confidence: 99%